Relationships Between (Step)Parents and Adult (Step)Children: Explaining Influences on Life Satisfaction and Marital Quality. Issue 6 (18th August 2017) - Lardier, David T.; Van Eeden-Moorefield, Brad; Nacer, Carly; Hull, Rachel; Browning, Scott
ABSTRACT: The purpose of this study was to examine important influences of adult (step)children's relationships with their biological fathers, biological mothers, and resident stepparents on their life satisfaction and marital quality and the moderating role of stepparent gender. The sample (N = 215) was from Wave 3 of the National Survey of Families and Households (NSFH). Results illustrate that (a) biological mothers and stepparents positively influenced life satisfaction among adult (step)children regardless of stepfamily type; and (b) that the influence of parent–child relationship quality on the adult child's marital quality did vary as a function of stepfamily type. Specifically, there was a positive link between current stepmother–child relationship quality and the focal child's current marital quality. The opposite link was found for those reared in stepfather households.